2018
DOI: 10.7150/jca.26073
|View full text |Cite
|
Sign up to set email alerts
|

FEZF1 is an Independent Predictive Factor for Recurrence and Promotes Cell Proliferation and Migration in Cervical Cancer

Abstract: The Fez family zinc finger protein 1 (FEZF1), a critical transcription factor in nervous system development, has been implicated in cancer progression recently. However, its clinical significance remains unknown. By analyzing gene expression data of eight most common cancer types from The Cancer Genome Atlas (TCGA), we found that FEZF1 prominently associated with the recurrence-free survival of cervical cancer patients (P<0.001) and was an independent diagnostic factor for cervical cancer recurrence (P=0.002).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that the Fez family zinc finger protein 1 (Fezf1) serves as an important transcription factor to mediate neurological development (Shimizu et al, 2010;Lan et al, 2018). Furthermore, Fezf1 regulated various cell processes in glioma cells by activating the AKT-ERK signaling pathway (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the Fez family zinc finger protein 1 (Fezf1) serves as an important transcription factor to mediate neurological development (Shimizu et al, 2010;Lan et al, 2018). Furthermore, Fezf1 regulated various cell processes in glioma cells by activating the AKT-ERK signaling pathway (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ERFE gene was demonstrated to be associated with OS in colon cancer using univariate Cox regression analysis (39). Of note, the FEZF1 gene is an independent predictive factor for cervical cancer recurrence and promotes cervical cancer cell migration and proliferation (40). Of note, SLC22A31 mRNA expression levels are associated with OS in right-sided colon cancer, as determined using TCGA data (39).…”
Section: Discussionmentioning
confidence: 99%
“…Many years of research have shown that FEZF1 plays a key role in the development of nervous system [14]. Recently, FEZF1 has also been implicated in the progression of tumorigenesis, including enhancing the proliferation and tumorigenicity of GC by binding and activating the oncogene K-ras [15], promoting cell migration and invasion of CRC cells [16], playing a carcinogenic role in CC by acting as a transcriptional activating factor in the Wnt pathway [17], facilitating the development of glioma cells by activating Akt-ERK pathway [18], and so on. Based on the enthusiasm for the study of the FE1 family, there are more and more reports about FEZF1-AS1.…”
Section: Characteristics and Discovery Of Fezf1-as1mentioning
confidence: 99%